Diversidad específica y su estado de conservación en las Lomas de Mangomarca, Perú - Rosales Benites (†), Marina (2024)
The specific diversity of the fragile ecosystem 'Lomas de Mangomarca,' located in the district of San Juan de Lurigancho (Lima, Peru), was characterized through the identification of lichen, bryophyte, vascular plant, reptile, bird, and mammal species. Emphasis was placed on the conservation status of the species inhabiting this ecosystem, in accordance with national regulations on threatened species. The threats to the Lomas ecosystem were assessed through direct field observations and the perceptions of local residents via surveys. Ten lichen species, four bryophytes, and 36 vascular plants were recorded, complemented by data from previous studies, totaling 67 species, 28 birds, three reptiles, and one mammal, of which 18 are endemic to Peru. At the global level, the conservation status of the species shows that 40 species are at risk of extinction, as included in the IUCN Global Red List, and eight species are nationally threatened. The main direct threat to the Lomas de Mangomarca ecosystem is habitat loss caused by urban expansion, while the indirect driver is weak governance in the Lomas. Conservation in this ecosystem is vital to prevent the local extinction of key species that inhabit these fragile ecosystems, as 35% of the recorded species are at risk of extinction globally, and there has been a 49% reduction in vegetation cover by 2020 compared to the year 2000.